2022
DOI: 10.1016/j.sjbs.2021.08.097
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the phytochemical composition, antioxidant and cytotoxicity of the leaves of Litsea elliptica Blume – An ethnomedicinal plant from Brunei Darussalam

Abstract: Litsea elliptica is traditionally believed to prevent and treat stomach ulcers, cancer, fever and headaches. This study investigates the phytochemical composition, antioxidant and cytotoxic effects of L. elliptica leaf extracts. The phytochemical content was determined via GCMS analysis and total phenolic content (TPC) and total flavonoid content (TFC) were analysed using the Folin-Ciocalteu and aluminium-chloride assays. Antioxidant activities were determined using the 2,2-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…This indicated that the toxic effect was due to the presence of antioxidant compounds, which contributed to reducing the number of HepG2 cell. These findings are consistent with previous studies that chitin had moderate antioxidant activity ( Goh et al, 2022 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This indicated that the toxic effect was due to the presence of antioxidant compounds, which contributed to reducing the number of HepG2 cell. These findings are consistent with previous studies that chitin had moderate antioxidant activity ( Goh et al, 2022 ).…”
Section: Discussionsupporting
confidence: 94%
“…Antioxidants often interacted with DPPH radicals through the mechanism of proton donation. The presence of concentrated unpaired electrons led to the formation of the chitin radical compound, which has very low energy and was significantly less reactive, thereby increasing the ability to suppress DPPH free radicals ( Goh et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%